Australian subtropical vegetation and wetland response to fire, climate and nutrient availability during the Holocene - Haidee Cadd; Michela Mariani; John Tibby; Jonathan Tyler; Cameron Barr; Melanie J. Leng; Patrick Moss; Richard Lewis; Tim Cohen; Sam Marx; Glenn B. McGregor; Jonathan C. Marshall; et al. (Journal of Quaternary Science, 2025)
The iconic sand dune systems of Minjerribah (North Stradbroke Island), in southeastern Queensland, Australia, host numerous lakes and swamps containing organic‐rich sediment deposits that record changes in climate, fire and surrounding vegetation. Palaeoenvironmental reconstructions from individual locations can provide insights into changes in the environment, but determining the regional extent of these changes is seldom possible from a single site. Multi‐site compilations help elucidate the geographical nature of environmental changes and determine if they are driven by local or regional forces. Here, a synthesis of palynological records from six Minjerribah wetlands using a muti‐tiered Monte Carlo empirical orthogonal function (EOF) analysis allows island‐wide patterns of vegetation change to be identified. Coherent changes in vegetation were recorded, with first‐order changes (EOF1) indicating a long‐term shift in vegetation composition from closed forests towards woodland and heath vegetation. A compilation of macroscopic and microscopic charcoal from the same sites shares coherent patterns of change with a rainfall record from the island, suggesting that regional fire occurrence between 7000 and 2000 cal a bp was driven primarily by long‐term variations in rainfall and its influence on biomass. Comparison with fire activity, rainfall, sedimentary carbon, nitrogen and dust records from Minjerribah suggests that regional vegetation changes occur primarily in response to long‐term changes in nutrients and increasing rainfall variability. This analysis highlights the multi‐millennial connection between vegetation composition, climate, nutrients and fire occurrence across the Holocene in subtropical environments.